A contingency lens on cloud provider management processes - Severin Oesterle; Jan Jöhnk; Robert Keller; Nils Urbach; Xin Yu (Business Research, 2020)
Traditional ways of managing information technology (IT) service providers are no longer applicable as companies use more and more services provisioned in the cloud. Therefore, organizations are looking for new ways to manage their relationship with cloud providers. The shift from IT-as-a-product to IT-as-a-service puts clients in a continued dependency on cloud service providers (CSPs), making provider management a critical factor for companies' success. In this paper, we (1) identify cloud-specific challenges in managing CSPs, (2) develop a corresponding process framework for CSP management, and (3) discuss and extend this framework. Our final cloud management framework comprises ten processes for effective CSP management based on a literature study and twelve expert interviews. Furthermore, we unpack three major contingency factors, i.e., client-provider ratio, specificity, and service delivery model, which influence the reasonability and configuration of the cloud management processes. Drawing on two specific cases from our interview study, we explicate the contingency factors' influence. Thus, our paper contributes to cloud sourcing research by deepening the understanding of client-provider relationships and by introducing a viable CSP management instrument contingent on three salient factors of cloud service provisioning.
Keywords: 650; Cloud computing; Cloud sourcing; IT sourcing; Providermanagement; Contingency theory; Interview study